Ecotonal gradients shape biodiversity of multiple estuarine taxa - Rebecca Oester; Benjamin Branoff; Johanna Biederbick; Luise Grüterich; Raphael Koll; Fay Lexmond; Nele Martens; Julian Mittmann-Goesele; Friederike Neiske; Widhi Putri; Sina Remmers; Diana Richter; et al. (Estuarine, Coastal and Shelf Science, 2026)

Characterizing canopy light penetration in black walnut (Juglans nigra) cultivars to inform selection for alley cropping - Benjamin Bishop; Fernando Torralbo; Nicholas A. Meier; Mark Coggeshall; Felix B. Fritschi; Ronald S. Revord (Agroforestry Systems, 2026)
Eastern black walnut ( Juglans nigra L.) is a nut-producing tree species that breaks dormancy late in the spring, allowing a winter alley crop to ripen before substantial canopy shade is formed. However, there is a high level of variation in the timing and structure of tree canopy development within the black walnut cultivar collection maintained at the University of Missouri Center for Agroforestry (UMCA). To identify cultivars with high levels of compatibility with winter alley cropping, we measured the amount of photosynthetically-active radiation transmitted (PARt) through the canopy. Eight physical traits were also measured to assess their relationship with light interception and to gain insight on characters that lead to greater understory light extinction. Significant differences between cultivars were seen in PARt, particularly on Julian date 132 (May 12) where a two-fold difference was observed in PARt between the most contrasting cultivars. Traits such as date of bud break, tree shape and live canopy ratio were associated with levels of PARt, providing preliminary support for strong component drivers of light displacement/penetration during spring. This study provides the first exploration of genetic variation in black walnut for above-ground compatibility with an understory crop, and in doing so, reports meaningful genetic variation exists for study and use. New context is reported for design of subsequent genetic, physiological, and plant-plant interaction studies. For example, there is not a negative relationship between leafing duration and fruit production, and late-leafing varieties, which are more suitable for agroforestry, remain productive in comparison to early-leafing ones. Additionally, these data may inform the selection or breeding of cultivars with improved complementary for alley cropping with winter grains, as well as management strategies (pruning) to improve light penetration in black walnut alley cropping systems.

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Polar cod early life stage exposure to potential oil spills in the Arctic - Frode B. Vikebø; Raymond Nepstad; Mateusz Matuszak; Edel S.U. Rikardsen; Benjamin J. Laurel; Sonnich Meier; Elena Eriksen; Johannes Röhrs; Kai H. Christensen; Malgorzata Smieszek-Rice; Alf Håkon Hoel; Mats Huserbråten (Aquatic Toxicology, 2025)

Schwall-Sunk-Sanierung: Strandungsversuche mit Forellenlarven aus natürlicher Reproduktion und Empfehlungen für die Planung von Sanierungsmaßnahmen - Steffen Schweizer; Matthias Meyer; Benjamin Berger; Basil Wagner; Maurus Meier; Jan Baumgartner; Robin Hochgesand; Peter Büsser; Lorenzo Gorla (WASSERWIRTSCHAFT, 2025)

Quantitative trait loci for bearing habit in a ‘Sparrow’ × ‘Schessler’ Juglans nigra mapping population - Benjamin Jablonski; Nicholas A. Meier; Warren Chatwin; Mark V. Coggeshall; Jeanne Romero-Severson; Ronald S. Revord (Tree Genetics & Genomes, 2024)
Eastern black walnut, Juglans nigra L., is an economically important tree species valued for its high-quality timber and edible nuts. A regional industry for the species’ nut and kernel products resides in Missouri, where over 9 million kg of hulled in-shell nuts are purchased in masting years. The crop is primarily based upon nuts harvested from wild trees, placing a ceiling on nut volume and quality (e.g. small nut size, dark pellicle color, and 10–14% kernel by weight). Orchards of named cultivars, like ‘Kwik Krop’ and ‘Sparrow’, supply up to 22,000 kg of nuts with a higher kernel percentage (> 26%) and improved quality. Such cultivars often represent chance wild or on-farm seedlings, clonally propagated since the late 1800’s by enthusiasts. Today, continued improvement of eastern black walnut as an orchard crop is limited by a long generation time, delayed expression of important traits, and space requirements – creating a strong need for marker-trait association studies that inform progeny selection. The first linkage map for J. nigra was recently created using the ‘Sparrow’ × ‘Schessler’ F 1 population and loci for phenology traits discovered. The objective of this study is to utilize these genetic resources to detect quantitative trait loci (QTL) and report associated DNA markers for the spur-bearing habit, which promotes precocity and high yield. Using single-year data from the 11-year-old population, we observe that segregation for the spur-bearing habit appears to be recessive and multigenic. Three QTLs (p > 0.99) were identified on linkage group (LG) 8, LG11, and LG16 that explain 7.2%, 8.7%, and 10% of trait variation, respectively. Regions between flanking DNA markers were 3.16 cM, 4.32 cM, and 9.69 cM, respectively. This study is the first to examine the genetic control of bearing habit and yield in eastern black walnut and informs breeders’ approach for their future genetic improvement.

L-PBF of the Metastable β Titanium Alloy Ti-5553: Microstructure and Mechanical Properties - Benjamin Meier; Jelena Petrusa; Wolfgang Waldhauser (BHM Berg- und Hüttenmännische Monatshefte, 2024)
Ti-5Al-5V-5Mo-3Cr or Ti-5553 is a metastable β Titanium alloy with excellent mechanical properties. Compared to the most common titanium alloy, the α and β Ti6Al4V, even at high cooling rates as present in the laser powder bed fusion process, it establishes an β dominant microstructure which is further highly tunable by heat treatment at lower temperatures than Ti6Al4V. In the scope of this contribution, the processability of T‑5553 is investigated, and the effects of stress relief heat treatment are evaluated. Its influence of achieved microstructures on hardness and impact strength is shown.

A review to frame the utilization of Eastern black walnut (Juglans nigra L.) cultivars in alley cropping systems - Benjamin Bishop; Nicholas A. Meier; Mark V. Coggeshall; Sarah T. Lovell; Ronald S. Revord (Agroforestry Systems, 2023)
Agroforestry adoptition is gaining considerable traction in the temperate US with growing popularity and government incentives (e.g., the Partnerships for Climate-Smart Commodities Project) for systems with greenhouse gas mitigation potential. The identification of complementary species combinations will accelerate the expansion of temperate agroforestry. Since the mid-19th century, European timber plantations have taken advantage of the late-leafing habit of walnut ( Juglans spp.) to grow a spring grain crop between the tree rows. Such alley cropping systems increase land-use efficiency and provide extensive environmental benefits. A parallel but underutilized opportunity in North American involves incorporating eastern black walnut ( Juglans nigra L.) cultivars into alley cropping systems (ACS). Eastern black walnut, henceforth referred to as black walnut, is native to North America and exhibits architectural and phenological characters for reduced competition with winter cereal crops grown in alleys. Black walnut also produces nutritious nuts, and cultivars with improved kernel percentage and mass offer potential to cultivate the species as a domesticated orchard crop, as opposed to just the high-quality timber for which it is well-known. However, field observations suggest significant variation in tree architecture and phenology amongst cultivars, which is likely to influence complementarity with winter grains. Comprehensive characterization of trait genetic diversity is needed to best leverage germplasm into productive systems. Here, we review literature related to implementing ACS with consideration of cultivar-dependent traits that may reduce interspecific competition. While the focus is directed toward black walnut, broad characterization of other underutilized fruit/nut species will allow for robust diversification of ACS.

High Temperature Tensile Strength of TI6AL4V Processed by L-PBF—Influence of Microstructure and Heat Treatment - Benjamin Meier; Fernando Warchomicka; Jelena Petrusa; Reinhard Kaindl; Wolfgang Waldhauser; Christof Sommitsch (BHM Berg- und Hüttenmännische Monatshefte, 2023)
Ti6Al4V is the most widely used α‑β Titanium alloy for application in medicine, automotive, and aerospace, known for its high strength and corrosion resistance, but also its high maximal operating temperature of around 420 °C. Combined with its decent weldability under a shield atmosphere it has become a standard alloy for additive manufacturing processes, especially laser and electron beam powder bed fusion (L-PBF). Although this material is well studied, the influence of the L‑PBF process on its tensile properties at elevated temperatures remains almost unexplored. For that reason, this contribution focuses on the analysis of the tensile properties of Ti6Al4V up to 500 °C for different heat treatments and compares it to aerospace standards. Furnace annealed samples reach a tensile strength between 1022 to 660 MPa from room temperature to 500 °C respectively, while stress-relieved specimens reach 1205 to 756 MPa. Stress-relieved samples show a lower ductility at room temperature, but elongation at break increases at high temperature and outperforms furnace annealed samples at 500 °C.

Investigating the overlapping associations of prior concussion, default mode connectivity, and executive function-based symptoms - Benjamin L. Brett; Andrew M. Bryant; Lezlie Y. España; Andrew R. Mayer; Timothy B. Meier (Brain Imaging and Behavior, 2022)

Movement of transposable elements contributes to cichlid diversity - Karen L. Carleton; Matthew A. Conte; Milan Malinsky; Sri Pratima Nandamuri; Benjamin A. Sandkam; Joana I. Meier; Salome Mwaiko; Ole Seehausen; Thomas D. Kocher (Molecular Ecology, 2020)
African cichlid fishes are a prime model for studying speciation mechanisms. Despite the development of extensive genomic resources, it has been difficult to determine which sources of genetic variation are responsible for cichlid phenotypic variation. One of their most variable phenotypes is visual sensitivity, with some of the largest spectral shifts among vertebrates. These shifts arise primarily from differential expression of seven cone opsin genes. By mapping expression quantitative trait loci (eQTL) in intergeneric crosses of Lake Malawi cichlids, we previously identified four causative genetic variants that correspond to indels in the promoters of either key transcription factors or an opsin gene. In this comprehensive study, we show that these indels are the result of the movement of transposable elements (TEs) that correlate with opsin expression variation across the Malawi flock. In tracking the evolutionary history of these particular indels, we found they are endemic to Lake Malawi, suggesting that these TEs are recently active and are segregating within the Malawi cichlid lineage. However, an independent indel has arisen at a similar genomic location in one locus outside of the Malawi flock. The convergence in TE movement suggests these loci are primed for TE insertion and subsequent deletions. Increased TE mobility may be associated with interspecific hybridization, which disrupts mechanisms of TE suppression. This might provide a link between cichlid hybridization and accelerated regulatory variation. Overall, our study suggests that TEs may be an important driver of key regulatory changes, facilitating rapid phenotypic change and possibly speciation in African cichlids.